2022
DOI: 10.1088/2515-7620/ac70ac
|View full text |Cite
|
Sign up to set email alerts
|

Comparing surface wind stress and sea surface temperature biases over the tropical and subtropical oceans in subsets of CMIP6 models categorized by frozen hydrometeors-radiation interactions

Abstract: We evaluate the simulations of surface wind stress (TAU) and sea surface temperature (SST) over subtropical and tropical Pacific and Atlantic oceans in subsets of CMIP6 models that are categorized by frozen hydrometeors-radiation interactions. The CMIP6 models are divided into two subsets with combined (SON1) and separated (SON2) radiative properties of cloud ice and falling ice (snow) and compared to the set with cloud ice radiative effects only (NOS). There is evidence that these hydrometeors-radiation inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…In particular, convective snow and stratiform + convective forms of rain are not included in our previous experiences (Li et al 2015(Li et al , 2016. We argue that including rain radiative effects might not have large impacts on the Pacific climates, but adding stratiform snow can have substantially changes the simulation of Pacific climate found by, for example, Li et al (2015Li et al ( , 2016Li et al ( , 2020bLi et al ( , 2022aLi et al ( , 2022b and Michibata et al (2019). It might be worth to separate the roles played by the stratiform and convective snow radiative effects and their impacts on the circulation-radiation coupling in GISS-E3.…”
Section: Summary and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In particular, convective snow and stratiform + convective forms of rain are not included in our previous experiences (Li et al 2015(Li et al , 2016. We argue that including rain radiative effects might not have large impacts on the Pacific climates, but adding stratiform snow can have substantially changes the simulation of Pacific climate found by, for example, Li et al (2015Li et al ( , 2016Li et al ( , 2020bLi et al ( , 2022aLi et al ( , 2022b and Michibata et al (2019). It might be worth to separate the roles played by the stratiform and convective snow radiative effects and their impacts on the circulation-radiation coupling in GISS-E3.…”
Section: Summary and Discussionmentioning
confidence: 93%
“…Li et al (2015Li et al ( , 2016 examined this mechanism by turning on and off falling ice radiative effects (FIREs) using fully-coupled historical runs of the CESM1-CAM5 following CMIP5 protocol. The FIREs-off experiment, which is the same experiment as most of the GCMs performed in the CMIP5/CMIP6, do not consider the radiative impacts of larger size (∼100 to 120 um) of snow that often result in further biases in the radiation fields (Waliser et al 2011, surface wind stress, sea surface temperatures and precipitation (Li et al 2014a(Li et al , 2014b(Li et al , 2016(Li et al , 2020a(Li et al , 2022a. For example, it has been reported that current coupled GCMs (e.g., CMIP5/CMIP6) show biases of underestimated TOA reflected shortwave radiation, excessive downward shortwave radiation at the surface and overestimated outgoing longwave radiation over precipitation active regions such as the ITCZ/SPCZ and TWP (e.g., Li et al 2013Li et al , 2014aLi et al , 2014bLi et al , 2020a.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to a weaker surface wind stress and decreasing upper ocean mixing, resulting in warmer SSTs over the trade-wind regions (Li et al 2014(Li et al , 2016(Li et al , 2018. The inclusion of FIREs is shown to improve the simulated tropical climate states of radiation fields, TAU and SST in CMIP5 and CMIP6 (Li et al 2014(Li et al , 2015(Li et al , 2022b and SSHA (Li et al 2020(Li et al , 2022a for the present-day climate simulation. Chen et al (2018) further illustrated that the radiation-circulation response to global warming would present similar patterns to those of the present-day climate simulations.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have investigated the present-day SSH in climate models and their ensembles, such as Community Earth System Model (CESM) (Fasullo and Nerem 2018), Coupled Model Intercomparison Project phase 5 (CMIP5) (Hay et al 2015, Widlansky et al 2015, Li et al 2022a, and CMIP6 (Dhage and Widlansky 2022). They all pointed out in common that the rising sea level is associated with warmer SST over certain regions, for example, the tropical Pacific is expected to have a higher rate of sea level rise compared to the global average changes of SSH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation